2016
DOI: 10.2967/jnumed.115.171454
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of 18F-PF-05270430, a Novel PET Radioligand for the Phosphodiesterase 2A Enzyme

Abstract: The enzyme phosphodiesterase 2A (PF-05270430) is a potential target for development of novel therapeutic agents for the treatment of cognitive impairments. The goal of the present study was to evaluate the PDE2A ligand 18 F-PF-05270430, 4-(3-fluoroazetidin- ,2,4]triazine, in nonhuman primates. Methods: 18 F-PF-05270430 was radiolabeled by 2 methods via nucleophilic substitution of its tosylate precursor. Tissue metabolite analysis in rodents and PET imaging in nonhuman primates under baseline and blocking cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 20 publications
(32 reference statements)
1
30
0
Order By: Relevance
“…18 F-PF-05270430 was prepared as described in the companion paper (6) and in the supplemental materials (available at http://jnm. snmjournals.org).…”
Section: Radiotracer Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…18 F-PF-05270430 was prepared as described in the companion paper (6) and in the supplemental materials (available at http://jnm. snmjournals.org).…”
Section: Radiotracer Synthesismentioning
confidence: 99%
“…The companion paper reports that the PET ligand 18 F-PF-05270430 is a potent inhibitor with high binding affinity for PDE2A (6). It shows excellent selectivity over other PDE subtypes and has good properties for PET imaging, as evaluated in nonhuman primates.…”
mentioning
confidence: 99%
“…In NHP, brain distribution concordant with PDE2A expression was found, and occupancy studies in NHP with PDE2A inhibitor PF-05180999 showed a decrease in V T of 32% and a maximum BP ND reduction of 72%, in high-binding regions (Table 4) [127]. However, in lower uptake regions (including the cerebellum as the reference region), V T increased upon blocking, with no hypothesis from the authors discussed [127].…”
Section: Selectivity Data For 18 F-pf-05270430mentioning
confidence: 94%
“…[122] [126]. Large non-specific binding in NHP brain [127]. Presence of metabolites in rat brain, cerebellum activity increased upon blocking [127].…”
Section: Histone Deacetylasementioning
confidence: 99%
See 1 more Smart Citation